2023
DOI: 10.3389/fimmu.2023.1120034
|View full text |Cite
|
Sign up to set email alerts
|

Advances in mechanism and regulation of PANoptosis: Prospects in disease treatment

Abstract: PANoptosis, a new research hotspot at the moment, is a cell death pattern in which pyroptosis, apoptosis, and necroptosis all occur in the same cell population. In essence, PANoptosis is a highly coordinated and dynamically balanced programmed inflammatory cell death pathway that combines the main features of pyroptosis, apoptosis, and necroptosis. Many variables, such as infection, injury, or self-defect, may be involved in the occurrence of PANoptosis, with the assembly and activation of the PANoptosome bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 126 publications
(197 reference statements)
0
22
0
Order By: Relevance
“…25 Evidence demonstrated that several tumors such as colorectal cancer and prostatic cancer were possibly associated with PANoptosis. 12 Despite this, there are few studies reporting the relationships between PANoptosis and LUAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Evidence demonstrated that several tumors such as colorectal cancer and prostatic cancer were possibly associated with PANoptosis. 12 Despite this, there are few studies reporting the relationships between PANoptosis and LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…11 The assembly and activation of PANoptosome are deemed an organic response of selfprotection to prevent against virus, bacterial and fungal infections in infectious diseases. 12 Other than for infection, PANoptosis may also be associated with the occurrence and development of cancer. 13 Abnormal cell death is an imperative pathological mechanism of tumor progress, and increasing numbers of studies indicate that PANoptosis is involved in this progress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the regulation of PANoptosis is very important for the protection of the human system. In terms of the mechanism of PANoptosis, its regulation can be mainly divided into three parts: recognition of DAMPs and PAMPs, formation of PANoptosome, and activation of execution proteins 100 . However, due to the diversity of both pattern recognition receptors on the cell surface and death execution proteins, it is difficult to achieve the regulation of the whole PANoptosis process by focusing on a single molecule.…”
Section: Regulation Of Panoptosismentioning
confidence: 99%
“…Despite the promising outlook of cancer therapies targeting PANoptosis, it is essential to note that treating cancer through PCD pathways and inflammatory signaling is a complex process closely tied to the specifics of the cancer type 100,146 . Therefore, selecting appropriate molecular targets for each specific cancer is critical, as different PCD pathways may perform different roles in various cancers.…”
Section: Cancer Therapy Through Panoptosismentioning
confidence: 99%